An infectious arterivirus cDNA clone: Identification of a replicase point mutation that abolishes discontinuous mRNA transcription - van Dinten, Leonie C. (The National Academy of Sciences of the USA, 1997)
Equine arteritis virus (EAV) is a positive-strand RNA virus that uses a discontinuous transcription mechanism to generate a nested set of six subgenomic mRNAs from which its structural genes are expressed. A stable bacterial plasmid (pEAV030) containing a full-length cDNA copy of the 12.7-kb EAV genome was constructed. After removal of a single point mutation in the replicase gene, RNA transcripts generated in vitro from pEAV030 were shown to be infectious upon electroporation into BHK-21 cells. A genetic marker mutation was introduced at the cDNA level and recovered from the genome of the progeny virus. The potential of pEAV030 as a tool to express foreign genes was demonstrated by the efficient expression of the chloramphenicol acetyltransferase (CAT) reporter gene from two different subgenomic mRNAs. The point mutation that initially rendered the full-length clone noninfectious was found to result in a particularly intriguing phenotype: RNA carrying this mutation can replicate efficiently but does not produce the subgenomic mRNAs required for structural protein expression. To our knowledge, this mutant provides the first evidence that the requirements for arterivirus genome replication and discontinuous mRNA synthesis are, at least partially, different and that these processes may be separated experimentally.